2016
DOI: 10.18869/acadpub.jafm.68.235.25270
|View full text |Cite
|
Sign up to set email alerts
|

On the Onset of Taylor Vortices in Finite-Length Cavity Subject to a Radial Oscillation Motion

Abstract: Taylor-Couette flow (TCF) is an important template for studying various mechanisms of the laminarturbulent transition of rotating fluid in enclosed cavity. It is also relevant to engineering applications like bearings, fluid mixing and filtration. Furthermore, this flow system is of potential importance for development of bio-separators employing Taylor vortices for enhancement of mass transfer. The fluid flowing in the annular gap between two rotating cylinders has been used as paradigm for the hydrodynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The study of the Taylor-Couette problem provides valuable insights into the fundamental aspects of fluid dynamics, such as stability, transition to turbulence, and the influence of boundary conditions on flow patterns. The problem has been extensively studied both experimentally and theoretically, and it continues to be a subject of active research in fluid mechanics [3,5,6,7,15,16,17]. In Micro-Electro-Mechanical Systems (MEMS), the Taylor-Couette problem can be relevant in certain applications involving rotating components or fluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the Taylor-Couette problem provides valuable insights into the fundamental aspects of fluid dynamics, such as stability, transition to turbulence, and the influence of boundary conditions on flow patterns. The problem has been extensively studied both experimentally and theoretically, and it continues to be a subject of active research in fluid mechanics [3,5,6,7,15,16,17]. In Micro-Electro-Mechanical Systems (MEMS), the Taylor-Couette problem can be relevant in certain applications involving rotating components or fluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…So far, an abundance of theoretical, experimental and numerical studies on the formation of Taylor vortices between two rotating cylinders, circular Couette flow, with either or both of them rotating have been presented with various geometric parameters, i.e., aspect ratio and radii ratio, focusing on the flow behavior and the transition to turbulence under different boundary conditions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The researchers have concluded that the various flow regimes occurring in the cylindrical Taylor-Couette system depend on the radii ratio and aspect ratio of this geometry.…”
Section: Introductionmentioning
confidence: 99%